The Impact of Cyber Attacks on National Data Centers on National Resilience: A Case Study of Soekarno Hatta Airport Immigration Checkpoints - Ikhtiram, Annisa Nuril; Hamad, Ibnu (Green Publisher Indonesia, 2025)
This study analyzes the impact of cyber attacks on the National Data Center (PDN) on national resilience, with a case study of the Immigration Checkpoint at Soekarno Hatta Airport. Cyber attacks on the PDN, which paralyzed the immigration system, exposed the vulnerabilities of digital infrastructure that is crucial to the continuity of public services. This study examines how disruptions to immigration services impact mobility, the economy, and the country's image. The economic impact is analyzed through potential losses due to flight delays, decreased tourism, and disruption to the supply chain. The social aspect is examined through the psychological impact on society due to uncertainty and discomfort. The weaknesses of the National Data Center (PDN) are not only understood as technical problems that disrupt administrative services, but also as issues that have a direct impact on the vital function of the Immigration Checkpoint (TPI). TPI has a strategic role in managing the flow of population migration, both Indonesian Citizens (WNI) and Foreign Citizens (WNA), who leave and enter through the country's border areas. Furthermore, this study explores how the attack affects public trust in the government's ability to protect vital data and infrastructure. The analysis of national resilience focuses on how cyber attacks can weaken the stability of the state and damage the government's ability to carry out its functions. This study emphasizes the need for investment in strengthening cybersecurity systems and increasing public awareness to minimize similar impacts in the future.